The effect of vitrified–warmed blastocyst transfer on postnatal growth: a 1-year follow-up questionnaire study. Issue 5 (May 2022) - Alteri, Alessandra; Campo, Giovanni; Pagliardini, Luca; Privitera, Laura; Cavoretto, Paolo Ivo; Candiani, Massimo; Papaleo, Enrico; Viganò, Paola
Abstract: Research question: Is postnatal growth of singletons aged 12 months born after vitrified–warmed blastocyst transfer (frozen embryo transfer [FET]) different from children born after fresh blastocyst transfer? Design: A retrospective cohort study conducted at a single university-affiliated obstetrics and fertility centre between 2014 and 2016. Women who underwent fresh transfer or FET at blastocyst stage and obtained a singleton live birth were included. Propensity score inverse probability weighting was used to balance baseline maternal characteristics between fresh and FET cycles. Results: Of the 382 women with singleton live births, 124 underwent a fresh blastocyst transfer and 258 underwent a FET. Significantly higher birth weight and length z-scores were observed after FET ( P = 0.01 and P = 0.002, respectively) compared with the fresh transfer group. At 12 months of age, the fresh and FET groups showed no significant effect on the weight z-score, but the FET was associated with a higher height z-score ( P = 0.001) compared with fresh blastocyst transfer. The comparison between males and females from the same study group showed higher birth weight z-score for males in the FET group ( P < 0.001). During the first 12 months, however, males in the FET group showed a slower growth trajectory in terms of weight ( P = 0.007). Conclusions: At 12 months of postnatal life, an increased height and sex-dependent differences in growth trajectories were observed in singletons born after FET compared with those born after fresh embryo transfer.